2021
DOI: 10.3168/jdsc.2021-0081
|View full text |Cite
|
Sign up to set email alerts
|

Trends in estimated intramammary antimicrobial usage in the Irish dairy industry from 2003 to 2019

Abstract: Understanding antimicrobial (AM) usage is key to safely reducing AM use in food-producing animals as part of addressing the global public health threat of AM resistance. We estimated intramammary AM usage from national sales data for the period 2003 to 2019, updating an earlier work. Descriptive trends in AM use are presented. We observed some reduction in dry cow AM use when accounting for cow numbers; however, use of blanket dry cow therapy is still widespread. In addition, there is evidence of ongoing use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 16 publications
0
19
0
1
Order By: Relevance
“…In Ireland, there are both challenges and opportunities in the coming period with the introduction of this Regulation. A substantial shift from current practice will be needed, both for PVPs and farmers, noting that there have been only tentative steps to this point towards selective DCT, a worrying recent upward drift in national sales of EMA Category B intramammary AMs (3rd and 4th generation cephalosporins) [ 7 ], and ongoing limited penetration of milk recording across the national herd [ 13 ]. Education will be critical to ensure a smooth transition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Ireland, there are both challenges and opportunities in the coming period with the introduction of this Regulation. A substantial shift from current practice will be needed, both for PVPs and farmers, noting that there have been only tentative steps to this point towards selective DCT, a worrying recent upward drift in national sales of EMA Category B intramammary AMs (3rd and 4th generation cephalosporins) [ 7 ], and ongoing limited penetration of milk recording across the national herd [ 13 ]. Education will be critical to ensure a smooth transition.…”
Section: Discussionmentioning
confidence: 99%
“…This remote (or so-called Schedule 8) prescribing is estimated to account for approximately 30% of all tubes prescribed for dry-cow therapy. There are ongoing concerns about the application of remote prescribing in Ireland, including by McAloon et al ([ 7 ]) who suggested that ‘this prescribing route is unlikely to provide the veterinary oversight necessary to support prudent prescription decision making on the basis of a detailed, on-farm understanding of mastitis and farm management’. AM stewardship is further compromised by the potential for Irish farmers to source intramammary AMs from multiple sources.…”
Section: National Measures To Support On-farm Am Stewardshipmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, intramammary (IM) AM sales data are currently the only feasible means to gain broad insights into on-farm usage of AMs relevant to mastitis control within the Irish dairy industry. Published information is available for the period 2003-19 [ 6 – 8 ], with key themes including near-universal blanket dry cow therapy across the national herd until very recently, a progressive fall in in-lactation therapy since 2013 (to a defined course dose (DCD)/cow of 0.43 in 2019), and ongoing concerns about both the use and trend in use of highest priority critically important AMs (HP CIA) in IM products, both with in-lactation and dry-cow therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the aim of this study was to update the earlier work of More et al [ 7 ] and McAloon et al [ 8 ] as a descriptive update of IM AM usage in the Irish dairy industry to include 2020 sales data. The data from 2013 to 2019 has already been reported and is included for reference purposes, reported comparisons are between 2019 and 2020 only.…”
Section: Introductionmentioning
confidence: 99%